Hormone replacement therapy enhances IGF‐1 signaling in skeletal muscle by diminishing miR‐182 and miR‐223 expressions: a study on postmenopausal monozygotic twin pairs. Issue 5 (18th July 2014) - Olivieri, Fabiola; Ahtiainen, Maarit; Lazzarini, Raffaella; Pöllänen, Eija; Capri, Miriam; Lorenzi, Maria; Fulgenzi, Gianluca; Albertini, Maria C.; Salvioli, Stefano; Alen, Markku J.; Kujala, Urho M.; Borghetti, Giulia; et al.
Summary MiRNAs are fine‐tuning modifiers of skeletal muscle regulation, but knowledge of their hormonal control is lacking. We used a co‐twin case–control study design, that is, monozygotic postmenopausal twin pairs discordant for estrogen‐based hormone replacement therapy (HRT) to explore estrogen‐dependent skeletal muscle regulation via miRNAs. MiRNA profiles were determined from vastus lateralis muscle of nine healthy 54–62‐years‐old monozygotic female twin pairs discordant for HRT (median 7 years). MCF‐7 cells, human myoblast cultures and mouse muscle experiments were used to confirm estrogen's causal role on the expression of specific miRNAs, their target mRNAs and proteins and finally the activation of related signaling pathway. Of the 230 miRNAs expressed at detectable levels in muscle samples, qPCR confirmed significantly lower miR‐182, miR‐223 and miR‐142‐3p expressions in HRT using than in their nonusing co‐twins. Insulin/IGF‐1 signaling emerged one common pathway targeted by these miRNAs. IGF‐1R and FOXO3A mRNA and protein were more abundantly expressed in muscle samples of HRT users than nonusers. In vitro assays confirmed effective targeting of miR‐182 and miR‐223 on IGF‐1R and FOXO3A mRNA as well as a dose‐dependent miR‐182 and miR‐223 down‐regulations concomitantly with up‐regulation of FOXO3A and IGF‐1R expression. Novel finding is the postmenopausal HRT‐reduced miRs‐182, miR‐223 and miR‐142‐3p expression in female skeletal muscle. The observed miRNA‐mediated enhancement of the target genes' IGF‐1R and FOXO3A expression as well as the activation of insulin/IGF‐1 pathway signaling via phosphorylation of AKT and mTOR is an important mechanism for positive estrogen impact on skeletal muscle of postmenopausal women.